The effect of routine ureteral stent placement on post-ureteroscopy complications: A prospective study from a resource limited setting. - Balagobi, B.; Sripandurangana, R.; Sivashankar, M.; Varothayan, S.; Dinoshiga, K.; Heerthikan, K.; Priyatharsan, K.; Vaishnavi, T.; Sureshka, G.M. (The College of Surgeons of Sri Lanka, 2023)
Rigid ureterorenoscopy (URS) stands as a highly successful treatment for ureteral stones. The current guidelines from the European Association of Urology (EAU) recommends selective double J (DJ) stent placement post-URS to mitigate major complications. However, in resource-limited hospital setups, executing selective stent placement poses substantial risks in preventing complications and reducing readmission rates. This study aims to unveil the ramifications of our routine stent replacement approach after ureteric stone surgery on surgical outcomes in a resource-constrained setting.
Keywords: DJ stent; Stone management; Ureterorenoscopy; Limited resource setting